The Effectiveness of Using Some Active Learning Strategies in the Developing of Rhetorical Skills Among First Grade Secondary Students in the Republic of Yemen - Ahmed, Fouad Hussein AlSalhi (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to find out the effect of using some active learning strategies in the developing rhetorical skills among first-grade secondary students in the capital Sana’a, based on the two approaches (descriptive and semi-experimental). To achieve the objective of the study, the researcher prepared a list of rhetorical skills, a test to measure skills, and an educational program based on active learning, The study sample consisted of (111). male and female students. the sample was divided into two groups (experimental and control groups). The research results showed the following: - There are statistically significant differences at the level (0.05). between the mean scores of the students of the experimental and control groups in the post application of the rhetorical skills test, in favor of the experimental group. - There are statistically significant differences at the level (0.05). between the mean scores of the experimental group students in the pre and post applications of the rhetorical skills test, in favor of the post application. - There are statistically significant differences at the level of significance (0.05). between the mean scores of male and female experimental group students in the post application of the rhetorical skills test, in favor of females.